The Impact of the Implementation of the Rice Distribution Policy by the Logistics Depot (DOLOG) on Community Welfare in Madello Village, Balusu District, Barru Regency ⁠ - Rahmi Rais; Sri Hardianti Lukman (Meraja journal, 2025)
[Full Paper] to pdf Copyright (c) 2025 Meraja journal